Impaired Lower Limb Proprioception in Spinocerebellar Ataxia Type 3 and Its Affected Factors - Liu, Xia-Hua; Wang, Zhi-Yong; Li, Ying; Xu, Hao-Ling; Sikandar, Arif; Ni, Jun; Gan, Shi-Rui (Frontiers in Neurology, 2022)
Background Spinocerebellar ataxia type 3 (SCA3) is one of the most common hereditary neurodegenerative diseases. Postural control dysfunction is the main symptom of SCA3, and the proprioceptive system is a critical sensory component of postural control. Accordingly, proprioception quantification assessment is necessary in monitoring the progression of SCA3. Objective We aimed to quantitatively assess lower limb proprioception and investigate the relationship between proprioception and clinical characteristics in patients with SCA3. Methods A total of 80 patients with SCA3 and 62 health controls were recruited, and their lower limb proprioception was measured using the Pro-kin system. Clinical characteristics of the SCA3 patients were collected. Multivariable linear regression was used to investigate potential affected factors for lower limb proprioception. Results We found that the patients with SCA3 experience poorer lower limb proprioception characterized by significant impairment in the average trace error (ATE) and time to carry out the test time execution (TTE) compared to controls (P < 0.05). Moreover, there were significant differences in TTE between the right and left lower limbs (P < 0.05) of the patients. Regression analyses revealed that increasing age at onset (AAO) predicts poorer lower limb proprioception for both ATE (β = 2.006, P = 0.027) and TTE (β = 1.712, P = 0.043) and increasing disease duration predicts poorer lower limb proprioception for ATE (β = 0.874, P = 0.044). AAO (β = 0.328, P = 0.019) along with the expanded alleles (β = 0.565, P = 0.000) could affect the severity of ataxia. By contrast, ATE (β = 0.036, P = 0.800) and TTE (β = −0.025, P = 0.862) showed no significant predictors. Conclusions Lower limb proprioception in patients with SCA3 is significantly impaired when compared to healthy controls. Increasing AAO and disease duration are related to impaired lower limb proprioception.